Incidence of Distant Metastasis in Head and Neck Cancer: A Hospital based Study - Prakriti Dayal; Ravikiran Ongole; Junaid Ahmed; Ceena Denny E; Deepali Agrawal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims and Objectives: To study the incidence of distant metastasis to bone and soft tissues from head andneck cancers and to assess the primary site of head and neck cancer, its clinical staging and its correlationwith the site of distant metastasis.Materials and Methods: Medical records of patients admitted for management of head and neck cancersin Medical and Radiation Oncology for a period of 6 years, were assessed for primary site of the tumour,staging, histopathological diagnosis and the site of distant metastasis.Results: Out of 125 patient records evaluated, the incidence of distant metastasis was 15.2%. Majority ofthe patients (60%) presented at Stage III and IV of the disease. Thyroid and tongue malignancies showed thehighest incidence of distant metastasis and this incidence was most common in the 5th and 6th decades of life.The most common sites of distant metastasis were to the bones (31.6%) and lungs (15.8%).Conclusion: Cancers of the head and neck is typically loco-regional in nature, with metastasis to cervicalnodes. Distant metastasis, though uncommon, may adversely impact the survival and quality of life of thepatient. Understanding the risk factors and incidence for metastatic head and neck cancers may be useful intreatment planning and follow-up protocols for newly diagnosed patients.